PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK DAISY ORGANIC DI KOTA BATAM - susanti, devi; Purba, Daris (SCIENTIA JOURNAL, 2021)
The purposing of this research is to know between promotion and product quality can effect to purchase decision either partially (T test) or simultaneously (F test) of Daisy Organic. Using three variable which consisting two variable independent which promotion as X1 and product quality as X2 and variable dependent which purchase decision as variable Y. In this research, technique data collection done by distributing questionnaire to the sample to be used is as many as 136 respondents. The method used in this research is descriptive method with quantitative approach and using SPSS software version 25 for data analysis. From the result showed that value of R square is 0,717 atau 71,7%, can be known from value the promotion and product quality affect to the purchase decision while 28,3% is the rest influenced by other variable that not included in this research model. based on result of T test for promotion equal to 4,403>1,65613 and significant 0.000 > 0.05 which mean promotion (X1) have significant effect to purchase decision and product quality (X2) has value 9,925>1,66023 is the sign that product quality have significant effect to purchase decision.